2001
DOI: 10.1089/108729001300338654
|View full text |Cite
|
Sign up to set email alerts
|

Best Minimally Modified Antisense Oligonucleotides According to Cell Nuclease Activity

Abstract: Minimally modified oligonucleotides belong to the second-generation antisense class. They are phosphodiester oligonucleotides with a minimum of phosphorothioate linkages in order to be protected against serum and cellular exonucleases and endonucleases. They activate RNase H, have weak interactions with proteins, and have thus a better antisense efficiency. Two of them have been designed from an all-phosphorothioate antisense oligonucleotide directed against mdr1-expressing cells. They are protected against se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 37 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Natural phosphodiester oligonucleotides are quickly digested by cellular nucleases in the cell (Djavanbakht Samani et al, 2001). Therefore, ASOs were modified to some forms that are nucleaseresistant and appropriate for research purposes ( 7c).…”
Section: Resultsmentioning
confidence: 99%
“…Natural phosphodiester oligonucleotides are quickly digested by cellular nucleases in the cell (Djavanbakht Samani et al, 2001). Therefore, ASOs were modified to some forms that are nucleaseresistant and appropriate for research purposes ( 7c).…”
Section: Resultsmentioning
confidence: 99%
“…One common method has been to cap the 3′- and/or 5′- ends of the nucleic acid strand [19], which prevents attacks by exonucleases. Endonucleases, however, appear to have a preference for pyrimidines, with cleavage occurring more frequently in the case of two or more adjacent pyrimidines [20,21]. One of the first types of modification introduced to enhance the stability of ASOs was the use of phosphorothioate nucleotides as an alternative backbone.…”
Section: Post-selex Structure Modificationmentioning
confidence: 99%
“…In the case of the phosphorothioate base, one of the non-bridging phosphate oxygens in the phosphodiester linkage is substituted for sulphur [22]. This has proven to be very effective in protecting ASOs against exonucleases when placed in the 5′- or 3′- end of the oligonucleotide, with it appearing to be most effective when placed at the 3′-side of the internal pyrimidine [20]. However, it has been suggested that these are “stickier” towards proteins than the normal phosphodiester backbone [23], which may present a problem with aptamers and non-specific binding.…”
Section: Post-selex Structure Modificationmentioning
confidence: 99%
“…Liang et al, 2017). Thus, secondary structures of three viral regions on SARS-CoV-2 genomic RNA; 5`UTR, start codon, and or 3`UTR as the target in ASO design were predicted using Natural phosphodiester oligonucleotides are quickly digested by cellular nucleases in the cell (DjavanbakhtSamani et al, 2001). Therefore, ASOs were modified to some forms that are nucleaseresistant and appropriate for research purposes (Table2).…”
mentioning
confidence: 99%